Проблеми використання 3d друку при виробництві БПЛА - Небрат, В. В.; Гусак, О. А.; Посвалюк, М. В. (ХНУРЕ, 2024)
The report examines the challenges of using 3D printing in the production of unmanned aerial vehicles (UAVs). Emphasis is placed on the significant time and cost expenditures associated with this technology, as well as the high production costs. The research also highlights the unstable quality of the products, which poses risks and additional material and time expenses for manufacturers. Shedding light on these aspects will aid in understanding and managing the problems associated with using 3D printing in UAV production.
Keywords: 3D друк; виробництво БПЛА